Semiotical analysis of Nikolay Karamzin’s “Letter to editor” - Snežko, Julija (Literatūra, 2008)
Depending on the goal set forth by different researchers one can find different methodological approaches to the heritage of Nikolay Karamzin, including his publicistic-critical works, which mainly were studied from the point of view of the history of ideas, social-cultural models and cultural semiotics. This article aims at showing the structure of meanings or, in other words, the organization of content in Nikolay Karamzin‘s “Letter to Editor“ (the introductory article to “Vestnik Evropy“, the very influential first Russian journal with political position independent from official circles) with the use of semiotical methodology worked out by A.-J. Greimas, focusing on the text itself and leaving the extratextual elements outside investigation. By analyzing of discursive and narrative levels of the text and the situation of énonciación the following conclusion was made: in comparison to Europe Russia appears to be young, powerful, gifted but lacking important spiritual/cultural competence (general name for this competence “taste“ is still in the stage of development) in order to become equal to elder Europe and to become consolidated/united/Russian subject on the level of feelings or spirituality, in other words to become nation. Literature and publishing of the journal serve as very important means in this process: the journal in which it was refused from the section of critique is prescribed to bring into effect paternalistic, gentil, regardful function, becouse the opposite function – severe critique – could be harmful to Russian subject.